Synthesis, Crystal Structure and Thermodynamic Properties of Tris(8-Quinolinolato-N,O)cobalt(III) Methanol - Dan, Wen-Yan; Di, You-Ying; Zhang, Dong-Mei; He, Dong-Hua; Liu, Yu-Pu (Asian Journal of Chemistry, 2010)
Tris(8-quinolinolato-N,O)cobalt(III) methanol (Co(C9H6NO)3·CH3OH) solvate, which may be a kind of potential organic light-emittings material was synthesized by solvonthermal synthesis. X-Ray crystallography, elemental analysis and chemical analysis were applied to characterize the structure and composition of the complex. Lattice energy of the complex was derived from its crystal data. Low-temperature heat capacities of Co(C9H6NO)3·CH3OH(s) were measured by a small sample precision automated adiabatic calorimeter over the temperature range from 78- 370 K. A polynomial equation of the heat capacities as a function of temperature was fitted by the least square method. Based on the fitted polynomial, the smoothed heat capacities and thermodynamic functions of the compound relative to the standard reference temperature 298.15 K were calculated and tabulated at intervals of 5 K.